Physics of thin films : advances in research and development. - Francombe, Maurice H.; Hoffman, Richard Walther (Academic Press, 1971)
Physics of Thin Films: Advances in Research and Development, Volume 6 reviews the rapid progress that has been made in research and development concerning the physics of thin films, with emphasis on metallic films. Topics covered include anodic oxide films, thin metal films and wires, and multilayer magnetic films. This volume is comprised of five chapters and begins with a discussion on the dielectric properties and the technique of plasma anodization which are relevant to the applications of anodic oxide films in electronic devices. Conduction, polarization, and dielectric breakdown effects.